2023
DOI: 10.1101/2023.01.18.524654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Killer cell contractility and cytotoxicity is driven by TLR3 agonist-mediated TAZ cytoplasmic sequestration

Abstract: The evolutionarily conserved YAP/TAZ mechano-responsive transcription cofactors regulate development and tumorigenesis. Here, we show for the first time that human natural killer (NK) cells specifically express TAZ but not YAP, and TAZ serves to limit NK cytotoxicity. The TLR3 agonist, hiltonol, was able to trigger cytoplasmic sequestration of TAZ, which increased NK cytotoxicity. Mechanistically, a low dose of hiltonol enhanced the intracellular contractility of NK cells accompanied by an increase in active R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…HNSCC is a common malignancy that often presents with locoregional disease and can spread to distant sites . Recent studies have shown that HNSCC cells express elevated levels of Toll-like receptor-3 (TLR-3), which is involved in the recognition of viral RNA and the activation of antitumor immunity. TLR3 is one of 10 members of the TLR family, which contains an extracellular domain that recognizes and binds to pathogen-associated molecular patterns and also a cytoplasmic tail which acts as residual for recruitment of TLR3 signal mediators. ,, …”
mentioning
confidence: 99%
“…HNSCC is a common malignancy that often presents with locoregional disease and can spread to distant sites . Recent studies have shown that HNSCC cells express elevated levels of Toll-like receptor-3 (TLR-3), which is involved in the recognition of viral RNA and the activation of antitumor immunity. TLR3 is one of 10 members of the TLR family, which contains an extracellular domain that recognizes and binds to pathogen-associated molecular patterns and also a cytoplasmic tail which acts as residual for recruitment of TLR3 signal mediators. ,, …”
mentioning
confidence: 99%